2016
DOI: 10.1007/s11255-016-1383-z
|View full text |Cite
|
Sign up to set email alerts
|

Does a history of bullying and abuse predict lower urinary tract symptoms, chronic pain, and sexual dysfunction?

Abstract: Women with a history of bullying, abuse, or both predict increased pelvic floor distress, urological symptoms, increased urogenital pain, and increased dyspareunia. Clinicians should screen for exposure to bullying or abuse in order to provide comprehensive resources to address these psychosocial issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The other studies were retrospective, cross-sectional in nature (n=3). Fourteen studies were conducted in the US [23][24][25][26][27][28][29][30][31][32][33][34][35][36], 2 in Germany [37,38], 1 in the Netherlands [39] and 1 in Hong Kong [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other studies were retrospective, cross-sectional in nature (n=3). Fourteen studies were conducted in the US [23][24][25][26][27][28][29][30][31][32][33][34][35][36], 2 in Germany [37,38], 1 in the Netherlands [39] and 1 in Hong Kong [40].…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of childhood sexual abuse significantly associated with urinary frequency (42.6%, odds ratio 1.74), with urgency (18.1%, odds ratio 1.95) and nocturia (32.8%, odds ratio 1.31). Prevalence of adolescent/adult sexual abuse significantly associated with urinary frequency (40.8%, odds ratio 1.56), with urgency (19.0%, odds ratio 2.09) and nocturia (33.0% , odds ratio 1.31) Not reported Nault et al [ 31 ] Retrospective chart review of consecutive new female patients in their 40s and 50s presenting to a women’s urology centre; ( n =380; mean age 50 years) divided into four groups according to history: (1) abuse and bullying; (2) bullying but not abuse; (3) abuse but not bullying; (4) neither SA: unvalidated questionnaires about: sexual health. LUT: Overactive Bladder Questionnaire (OABq-SF), PFDI-20, UDI-6, CRADI-8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence of voiding difficulties amongst victims of sexual abuse has been poorly explored and Williams et al have reported a case of episodic urinary retention in a woman who experienced recurrent sexual trauma. Other pelvic symptoms reported by individuals who have experienced abuse include pelvic pain, dyspareunia, and symptoms of prolapse …”
Section: Resultsmentioning
confidence: 99%
“…Abuse is identified as a potential risk factor for CPP, 4 but only a few previous studies have provided information on the occurrence of abuse and associations with health status in women with CPP. 31,39,40 Women with a history of bullying or abuse have been shown to have poorer scores on both somatic and psychological health measures, 39 and several reports indicate that exposure to abuse of any kind can lead to a higher risk of poor health later in life. 31,[40][41][42] This is in agreement with our findings showing more symptoms of anxiety or depression and more SHCs among women exposed to abuse.…”
Section: Discussionmentioning
confidence: 99%